Carbon Emissions and Sequestration Due to Land Conversion In The Padang Watershed, North Sumatera (incomplete) - Suci Arisa Purba; Bejo Slamet; Abdul Rauf (Jurnal Serambi Engineering, 2021)
Land conversion activities cause changes in the area of vegetation and carbon storage in the air. These changes can lead to emissions (reduction of carbon stocks) or sequestration (addition of carbon stocks). This study aims to calculate stored carbon in the Padang watershed in 2009 and 2019 and to determine the dynamics of emissions and carbon sequestration due to land conversion in the Padang watershed, North Sumatra Province from 2009 to 2019. The method used in this research is spatial data processing using software Arc Gis. Processing, interpretation and classification of land cover are obtained from land cover data for 2009 and 2019 from the Ministry of Environment and Forestry. Furthermore, the analysis of emissions and carbon sequestration in the Padang watershed was carried out using the REDD Abacus SP software. The results showed that the total carbon stored in 2009 was 5,168,464.09 tons. Meanwhile, the total carbon stored in 2019 was 5,150,784.81 tons. This means that there is a decrease or carbon emission during the 2009-2019 period of 17,679.28 tons. The total net emissions and sequestration that occurred in the Padang watershed due to changes in land use from 2009 - 2019 were 22,851,751.43 tonnes CO2-eq / year and  3,100,199.00 tonnes CO2-eq / year, respectively. Efforts to reduce emissions include planting and developing forests and community-based forest management.